Challenges in sustainability reporting: evidence from Malaysia / Ho Wai Kee … [et al.] - Kee, Ho Wai; K. Suppiah, Susela Devi; Mohd Sidik, Vivi Norazlina; Kanagasabapathy, Shenba (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This paper aims to explore the challenges faced by companies in preparing a sustainability report. Interviews were conducted with the preparers of the sustainability report, consultants and directors from Malaysian public-listed companies. The findings of this study show that sustainability reporting can be hindered by the challenges faced by companies. Analysis of the interview transcripts revealed six key challenges. These include lack of board leadership, lack of board expertise, lack of management expertise, negative attitudes towards sustainability, difficulty to quantify sustainability impact and lack of an effective information system. This study provides practical guidance to companies and policy-makers on the challenges that need to be addressed to accelerate the sustainability reporting process. However, the sustainability issues discussed in this study is from the internal stakeholders’ perspective. We need to explore the sustainability issues from the external stakeholders’ perspective in our future study as these issues may further add to our understanding of the sustainability reporting process.